A personagem negra na obra infantil e juvenil de Joel Rufino dos Santos (1941-2015) - Adewole, Adeola Aiyedun [UNESP] (2025)
In his works of children’s and youth literature, Joel Rufino dos Santos (1941-2015) presented a new perspective on some historical figures and moments of Brazil, in relation to the literary production in the area usually performed by many of his contemporaries. He has chosen as his main focus the African myths and the representation of historical black characters through fiction. The author, also a history teacher, sought to rescue the voice of black characters systematically erased throughout the history of Brazil, returning its production to readers in training. The present work analyzes some children’s and youth works of the author with particular focus on the construction elements of black characters in the fictional narratives that he produced, representing historical characters and Afro-Brazilian mythical figures. The works analyzed will be O presente de Ossanha (2000); O Soldado que não era (1980), Gosto de África - histórias de lá e daqui (2000) and Quando eu voltei, tive uma surpresa (2000). We will also consider the general contribution of the author’s works in the aspect of children and youth literature.